The iPhone pocket guide : all the secrets of the iPhone, pocket sized - Breen, Christopher (Berkeley, Calif. : Peachpit Press, 2007)
Looks at the diverse capabilities of the iPhone, covering such topics as e-mail, Web browsing, maps, search functions, making phone calls and accessing the address book, and navigating through music, TV shows, and movies
Includes index
Keywords: iPhone (Smartphone); Cellular telephones -- Technological innovations; Internet telephony; Mobile computing